2013
DOI: 10.1111/apa.12130
|View full text |Cite
|
Sign up to set email alerts
|

Perfusion index and its dynamic changes in preterm neonates with patent ductus arteriosus

Abstract: Ductal persistence and flow pattern did not affect PI but did affect PVI in preterm neonates of less than 29 weeks of GA. Future studies are needed to establish the usefulness of PVI in the early detection and management of PDA in preterm neonates.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
30
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(38 citation statements)
references
References 32 publications
4
30
2
Order By: Relevance
“…Earlier studies have shown conflicting results concerning the effect of hsPDA on PI [20,21]. In the current study, there was a positive association with PI during the first 24 h and from 37 h onwards (when taking into account the hsPDA × time interaction) as also found by others [20].…”
Section: Discussionsupporting
confidence: 79%
“…Earlier studies have shown conflicting results concerning the effect of hsPDA on PI [20,21]. In the current study, there was a positive association with PI during the first 24 h and from 37 h onwards (when taking into account the hsPDA × time interaction) as also found by others [20].…”
Section: Discussionsupporting
confidence: 79%
“…Hakan et al reported a median PI value of 0.88(0.6, 1.26) in a cohort of 45 preterm infants [14] and Vidal et al found a median PI of 0.70 (0.50, 1.05) in a similar number of preterm infants [15]. We describe slightly higher values in preterm infants immediately after birth, 1.3 (0.86, 1.68).…”
Section: Discussioncontrasting
confidence: 41%
“…It has also been shown that PI is highly reproducible in preterm infants [12], that this value increases over the first 3 days of life [10,13], and that PI may stabilise within 5 days of life [14]. Normative PI values have been described for preterm infants in the first day of life [14,15]. However, to our knowledge, PI values immediately after birth have not previously been determined.…”
Section: Contents Lists Available At Sciencedirectmentioning
confidence: 98%
“…Consequently, they propose that the age of the neonates should be taken into account for its clinical application. A study in preterm neonates with a haemodynamically important persistent ductus arteriosus also established different PI values depending on the neonate age that were not influenced by ductal flow pattern, with a median PI value of 0.7% in the first day of life (0.5–1.05%) and 1.5% (1.0–2.0%) on the seventh (p < 0.01). PI has also been proven to vary, specially in very preterm infants, depending on the placement of the pulse oximeter , being higher in the upper limbs (right upper limb = 0.92% vs. lower limb = 0.69%, mean difference = 0.24%, p < 0.001), fact probably related to the transitioning circulation in this population where patent ductus arteriosus is not uncommon, and the position of the low birthweight newborn, presenting a higher PI in prone sleeping position (mean PI value 3.7 ± 0.9% vs. PI 3.1 ± 0.7%).…”
Section: Resultsmentioning
confidence: 88%